Achievement emotions for mathematics questionnaire in senior high school: Validity and reliability for Indonesian students - Suparman; Juandi, Dadang; Turmudi; Avip Priatna Martadiputra, Bambang (COUNS-EDU: The International Journal of Counseling and Education, 2025)
Achievement emotions are recognized as key factors influencing students' success in mathematics. However, no Achievement Emotions Questionnaire for Mathematics (AEQ-M) specifically tailored for Indonesian senior high school students has been developed. This study aims to translate the 68-item AEQ-M into Indonesian and validate its use for senior high school students in Indonesia, termed AEQ-M-SHS-I. A purposive cluster sampling method was used to select 198 tenth and eleventh-grade students in West Java, Indonesia. Data analysis included descriptive statistics, item analysis, and reliability testing. Structural, convergent, and discriminant validity were assessed using confirmatory factor analysis (CFA). All of data analyses were supported by SPSS 26.0 and AMOS 26.0. The Indonesian AEQ-M-SHS-I consists of ten factors and 68 items, all demonstrating good discriminant validity. CFA showed good structural model fit indices (e.g., X²/df = 2.245, CFI = 0.937, TLI = 0.950, SRMR = 0.059, RMSEA = 0.079). Moreover, all of ten emotions in the AEQ-M-SHS-I had ideal convergent validity. Additionally, the tool exhibited high internal consistency (? = 0.868). These results indicate that the AEQ-M-SHS-I is a valid and reliable instrument for assessing achievement emotions in mathematics among Indonesian senior high school students.